Interview with Ken Schwartz, October 23, 1971 (Mustang Radio Network, 1971)
[00:00:09] Introduces Ken Schwartz, Director for Curriculum and Advisement for School of Architecture and Environmental Design [00:00:41] Schwartz talks about various public service projects that architecture students have recently participated in [00:01:41] Schwartz talks about how the students get started and fulfill the projects like those he listed [00:02:54] Schwartz talks about faculty and other architects guiding students in their work [00:03:22] Schwartz discusses how the students can be catalyst for professional services by being a source of enthusiastic and creative ideas [00:04:39] Schwartz talks about the student body of the School of Architecture and Environmental Design [00:05:44] Schwartz talks about the response of city government to the work done by students [00:06:50] Interviewer starts to wrap up interview